Innovative Strategies for Improving Energy Efficiency and Thermal Comfort in Heritage Buildings: A Case Study of Lawang Sewu - Gbran, Hassan; Rukayah, Siti; Suprapti, Atiek; Pandelaki, Edward Endrianto (Journal of Architectural Research and Design Studies, 2026)
This study introduces a novel integration of dynamic electrochromic glazing and CIGS photovoltaics tailored to the tropical heritage context of Lawang Sewu, aiming to provide a replicable retrofit model for similar Southeast Asian climates, focusing on Lawang Sewu, a colonial-era landmark in Semarang, Indonesia. The research integrates field measurements, simulation analyses, and retrofit modelling to assess indoor environmental quality across four functionally distinct rooms over one year. Retrofit interventions included electrochromic glazing, energy recovery ventilation, and Copper Indium Gallium Selenide (CIGS) photovoltaic systems—a flexible thin-film solar technology suitable for heritage facades. Results revealed that electrochromic glazing reduced heating demands, while PV integration achieved up to 90.46% annual energy savings. Seasonal variation and occupancy patterns were found to significantly influence thermal conditions. The PA_RN package—combining passive and renewable solutions—was identified as the optimal retrofit approach, balancing energy performance, thermal comfort, and heritage aesthetics. The study underscores the potential for achieving sustainability in heritage structures through context-sensitive retrofitting, offering a replicable model for similar buildings in tropical climates.